The Correlation of the Nurses Caring Behavior with Parents Anxiety Level Related to Invasive Procedures to Pediactric Patients - Dwi Wahyuni; Anisah Ardiana; Ahmad Rifai (Faculty of Nursing, Universitas Jember, 2020)
Hospitalization causes children to have received various treatments in the hospital such as invasive procedures. Hospitalization results in anxiety either to children or parents. Parental anxiety could be decreased by nurses' caring behavior This research aimed to analyze the correlation between nurses' caring behavior with parents' anxiety levels related to an invasive procedure to child patients in RSUD dr. Haryoto Lumajang. The research design was correlational descriptive with a cross-sectional approach. Purposive sampling was used with criteria of parents who have experience accompanying invasive procedures in children with a minimum stay of 1 day. A total of 112 parents with a hospitalized child were included. This study showed that participants had high perceptions of caring behaviors and 91% of parents hadn't anxiety. The result of Kendall tau b correlation test showed that p-value 0.036 (α = 0.05) and τ = -0.164. This study found that nurses’ caring behavior correlated to parents' anxiety level related to an invasive procedure to child patients in RSUD dr. Haryoto Lumajang. The correlation results show a very weak relationship, higher nurses’ caring lower parents’ anxiety. This study indicated that nurses’ caring behavior can reduce parents’ anxiety. The application of caring behavior should be improved, particularly in pediatric nursing as one of the vulnerable groups. So, caring as the essence of nursing can be achieved.